Analisis Pengaruh Penggunaan Media Video pada Pembelajaran IPA - Ndraha, Fita Kristiani; Harefa, Linda Wati; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of the use of video media on science learning. This study uses a literature review method that collects relevant journals. Journal references are obtained using the publish or perish application which assists researchers in finding relevant journals. Publish or Perish which allows users to conduct academic analysis quickly and effectively. Google Scholar is used as the data source for Publish or Perish. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the use of video media in junior high school learning can help students understand the concepts of science learning. Video media can visualize abstract ideas to be more concrete and easier for students to understand. Students will be more motivated to learn if there are interesting animations and visualizations